Increasing Teacher Participation in Using Digital Literacy with Interactive Animation Media in Thematic Learning Through In-House Training at Tegalharjo State Elementary School for the 2022/2023 Academic Year - Suprihatin, Suprihatin (IJCER (International Journal of Chemistry Education Research), 2024)
The aim of this research is to improve teachers' ability to use digital literacy with animated interactive media and to increase participant participation in taking In-House Training (IHT) at Tegalharjo Kapanewon Kalibawang Elementary School, Kulon Progo Regency. This research is school action research carried out at Tegalharjo Kapanewon Kalibawang Elementary School, Kulon Progo Regency. Data techniques and analysis use observation sheets and assessment instruments. This research was conducted in 2 cycles where each cycle consisted of 2 meetings. Participants' participation in taking part in the IHT each cycle has increased, in the first cycle of the 1st meeting and the 2nd meeting there was an increase of 13.22%. Meanwhile, in cycle II for the 1st meeting and the 2nd meeting there was an increase of 6.28%. The use of animated interactive media in cycle I for the 1st and 2nd meetings reached 12.50%. Cycle I at the 2nd meeting and Cycle II at the 1st meeting reached 5.13%. Furthermore, in cycle II of the 1st meeting and cycle II of the 2nd meeting there was an increase of 6.10%. Regarding IHT management by researchers in cycle I for the 1st and 2nd meetings, there was an increase of 5.42%. Furthermore, cycle I at the 2nd meeting with cycle II at the 1st meeting achieved an increase of 5.62%. In cycle II, at the 1st and 2nd meetings, there was an increase of 5.63%. So it can be said that teacher participation and ability to use digital literacy with animated interactive media through IHT activities can increase.